High Protective Efficacy of Probiotics and Rice Bran against Human Norovirus Infection and Diarrhea in Gnotobiotic Pigs - Lei, Shaohua; Ramesh, Ashwin; Twitchell, Erica; Wen, Ke; Bui, Tammy; Weiss, Mariah; Yang, Xingdong; Kocher, Jacob; Li, Guohua; Giri-Rachman, Ernawati; Trang, Nguyen Van; Jiang, Xi; et al. (Frontiers in Microbiology, 2016)
Probiotics have been recognized as vaccine adjuvants and therapeutic agents to treat acute gastroenteritis in children. We previously showed that rice bran reduced human rotavirus diarrhea in gnotobiotic pigs. Human noroviruses (HuNoVs) are the major pathogens causing nonbacterial acute gastroenteritis worldwide. In this study, Lactobacillus rhamnosus GG (LGG) and Escherichia coli Nissle 1917 (EcN) were first screened for their ability to bind HuNoV P particles and virions derived from clinical samples containing HuNoV genotype GII.3 and GII.4, then the effects of LGG+EcN and rice bran on HuNoV infection and diarrhea were investigated using the gnotobiotic pig model. While LGG+EcN colonization inhibited HuNoV shedding, probiotic cocktail regimens in which rice bran feeding started 7 days prior to or 1 day after viral inoculation in the LGG+EcN colonized gnotobiotic pigs exhibited high protection against HuNoV diarrhea and shedding, characterized by significantly reduced incidence (89% versus 20%) and shorter mean duration of diarrhea (2.2 versus 0.2 days), as well as shorter mean duration of virus shedding (3.2 versus 1.0 days). In both probiotic cocktail groups, the diarrhea reduction rates were 78% compared with the control group, and diarrhea severity was reduced as demonstrated by the significantly lower cumulative fecal scores. The high protective efficacy of the probiotic cocktail regimens was attributed to stimulation of IFN-γ+ T cell responses, increased production of intestinal IgA and IgG, and maintenance of healthy intestinal morphology (manifested as longer villi compared with the control group). Therefore, probiotic cocktail regimens containing LGG+EcN and rice bran may represent highly efficacious strategies to prevent and treat HuNoV gastroenteritis, and potentially other human enteric pathogens.